Effect of Botulinum Toxin Injection on the Progression of Hip Dislocation in Patients with Spastic Cerebral Palsy: A Pilot Study - Yookyung Lee; Seungeun Lee; Joonyoung Jang; Jiwoon Lim; Ju Seok Ryu (Toxins, 2021)
Hip adductor spasticity is a contributing factor to hip dislocation in patients with cerebral palsy (CP). We hypothesized that botulinum toxin injected into the hip adductor muscles would reduce spasticity and help prevent hip dislocation. Twenty patients with bilateral spastic CP aged 2 to 10 years with gross motor function classification system level IV or V were included. Botulinum toxin was injected into the hip adductor muscles at baseline and at 6-month follow-up. Muscle tone was measured with an eight-channel surface electromyography (EMG) recorder. A hip X-ray was performed, and Reimer’s hip migration index (MI) was measured. The Wilcoxon signed-rank test was used to compare the surface EMG values of the hip muscles at baseline and follow-up. The mean root mean square surface EMG value of the hip adductor muscles was significantly reduced at 1, 2, 3, and 7 months after the first injection, up to approximately 53% of the baseline. The 1-year progression of the hip MI was −0.04%. Repeated sessions of botulinum toxin injections at the hip adductor muscles significantly reduced muscle tone and hip displacement. A botulinum toxin injection may be used as an adjunctive treatment in the prevention of hip dislocation.